CULTURAL VALUES REFLECTED IN ENGLISH AND UZBEK PROVERBS: A COMPARATIVE STUDY - B.Tog’ayev,; S.Sattorova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the cultural values reflected in English and Uzbek proverbs from a comparative point of view. The topic is important because proverbs are not only short fixed expressions. They also preserve social memory, moral advice, and national ways of thinking. The article analyzes how common values such as work, honesty, patience,  friendship,  family,  and  mutual  help  are  expressed  in  the  two  proverb traditions. Attention is also given to differences in worldview. English proverbs often sound brief, practical, and individual-centered, while Uzbek proverbs more often stress family  ties,  collective  life,  respect,  and  hospitality.  The  study  uses  comparative, descriptive,  and  contextual  methods.  Proverbs  are  grouped  by  theme,  compared  in meaning and form, and then discussed as cultural signs. The discussion section includes selected proverb extracts with short analysis and footnote support. The results show that many values are shared by both cultures, but the way they are presented depends on each person’s social experience and national mentality. The article concludes that proverbs are a useful source for studying language and culture together, and they can also  support  comparative  linguistics,  translation  studies,  and  foreign  language teaching.